Complexity economic indexes for the energy market: Evidence during extreme global changes - Song, Pengcheng; Wang, Pang Paul; Zhang, Baozhen; Zhang, Xuan; Zong, Xiangyu (Energy economics, 2021)
This paper extends the complex economic index to measure the energy dependence of each country’s industrial structure, subject to the global trade framework. The Energy Dependence Competitiveness (EDC) Index and Energy Layout Complexity (ELC) Index are proposed, based on the Competitiveness and Economic Fitness (EF) algorithm. EDC reveals the industrial competitiveness of each country that relies on high energy-dependent industries. ELC reflects the fraction of energy-dependent industries involved in competitive industries. The empirical results show that EDC and ELC indices provide good explanations of economic performance, endowments and energy industries’ structure before, during and after the extreme change in the Energy Market in 2008. •This paper extends the complex economic index to the energy industry.•This paper studies changes and impacts on countries’ energy-dependent competitiveness during the financial crisis.•We construct two indicators: The Energy Dependence Competitiveness (EDC) Index and the Energy Layout Complexity (ELC) Index.•We find that the financial crisis created significant shocks on energy-dependent industries across countries.•We find that EDC and ELC have good ability to explain global energy trade and economic performance.